Pembelian impulsif di era digital: Peran live streaming, content marketing, dan ulasan pelanggan online pada pengguna Shopee - Mariana, Septanus Rita; Susilowati, Heni (Journal of Management and Digital Business, 2025)
Digital transformation has reshaped the global trade landscape, with e-commerce in Indonesia experiencing rapid growth. Impulse buying decisions in the digital context have become a dominant phenomenon. This study aims to analyze the influence of live streaming, content marketing, and online customer reviews on impulse buying behavior among Shopee users, as well as to identify the underlying psychological mechanisms of these relationships. The research adopts a quantitative paradigm with a descriptive design. The sample consists of active Shopee users in Bantul Regency, selected using an accidental sampling method. Data were collected through questionnaires and analyzed using multiple linear regression. The findings indicate that online customer reviews have the strongest influence on impulse buying on Shopee, followed by live streaming and content marketing. All three variables are proven to have a significant joint effect on impulse buying decisions. To optimize impulse buying on the Shopee platform, businesses should strategically leverage positive customer reviews and enhance interactive live-streaming features to increase consumer purchasing interest.